Teaching Factory and Technopark as a Driver of Enterpreneurship and Innovation: A Lesson Case Study From Indonesian’s Vocational Schools - Fitriani, Somariah (AL-ISHLAH: Jurnal Pendidikan, 2024)
To enhance the quality of vocational education, the Indonesian government has prioritized two projects: Teaching Factory and Technopark. Teaching factory model integrates vocational school learning with industry standards and   procedures in a setting that mirrors real world industrial environments. Technopark serves as the hubs of several teaching factories connecting industry, educational institutions and pertinent agencies to foster collaboration. These two initiatives are intertwined and interdependent one another. The study's objective was to explore the impacts of the deployment of the teaching factory and technopark to students’ skills, educational outcomes and their teachers’ competencies. Data were garnered from four public vocational high schools in Indonesia through non participant observation and semi structure interviews involving principals, curriculum vice principals, teaching factory coordinators and seven students. Research has revealed that pupils developed their creativity by producing items such as wooden products, and drone and enhanced their entrepreneurship skill by creating startups and selling product online selling. The study's findings suggest that government policies should promote stronger industrial relations and involve industry in designing vocational school curricula to meet national and international industry standards.